2023
DOI: 10.1021/acs.macromol.2c02558
|View full text |Cite
|
Sign up to set email alerts
|

Toughening and Stiffening in Thermoreversible Diels–Alder Polymer Network Blends

Abstract: The thermophysical properties, mechanical behavior, and healing performance of Diels–Alder-based polymer networks can be tuned widely by changing the molar mass, functionality, and stoichiometric ratio of the multifunctional diene (e.g., furan) and dienophile (e.g., maleimide) monomers. Blending furan-functionalized monomers with a high and low molar mass opens a new dimension in tuning the properties of the resulting reversible polymer network blends (RPNBs), containing different ratios of elastomeric and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Stress relaxation experiments were carried out at 90 °C (below the T gel value of the networks) and 30 °C for pristine networks and their CB-filled and hybrid composites, by applying 1% strain amplitude. At high temperatures (90 °C), for all filled and unfilled networks, the normalized relaxation modulus ( G / G 0 ), shown as a function of the logarithmic timescale, exhibits a decay over time and finally approaches zero (Figure c) . The stress relaxation is much accelerated for pristine networks, which is indicated by the faster decay of normalized modulus or in other words shorter relaxation time (τ).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Stress relaxation experiments were carried out at 90 °C (below the T gel value of the networks) and 30 °C for pristine networks and their CB-filled and hybrid composites, by applying 1% strain amplitude. At high temperatures (90 °C), for all filled and unfilled networks, the normalized relaxation modulus ( G / G 0 ), shown as a function of the logarithmic timescale, exhibits a decay over time and finally approaches zero (Figure c) . The stress relaxation is much accelerated for pristine networks, which is indicated by the faster decay of normalized modulus or in other words shorter relaxation time (τ).…”
Section: Resultsmentioning
confidence: 94%
“…Moreover, comparing the electrical conductivity values in two selected networks suggests that either different chemistry or network architecture (here, cross-linked density) may affect the development of filler networks drastically as the second reason. In general, for polymer composites, the percolation threshold depends on the aspect ratio of the fillers, the mixing process, and finally the characteristics of the matrix, which is the focus of this study. , Many studies have shown the effect of the polymer matrix to have a significant effect on the electrical conductivity. In addition to the chemistry of the polymer matrix, a higher degree of cross-linking can increase the number of charging groups or increase electric channels by the connection of neighboring carbon blacks by the shrinkage of cross-linked chains ascribed to rubber elasticity .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It suggests that the fracture mechanics of DPBM-FD4000_r0.7 (yellow) are much more comparable to Ecoflex 00-30 (gray); in particular, its high elongation up to more than 400% strain while DPBM-FS5000_r0.7 (seaweed green) has a lower elongation up to 160% strain. Combining these two networks that one benefits from high elongation (PPO) and the other benefits from higher tensile strength (PDMS) in blends, enables intermediate properties with adjusted Young’s modulus, stress, and strain at break depending on the percentages of PPO and PDMS backbones; it means that by combining these two furan-functionalized chains that have incompatible chemistries, the mechanical properties of blends can be tuned from relatively tough elastomers to more flexible elastomers . In other words, changing the composition of two polymers in blends allows sweeping the mechanical properties over a wider range of properties.…”
Section: Results and Discussionmentioning
confidence: 99%